Handover Algorithms for Enhanced Throughput in a Hybrid OMA-NOMA System with Imperfect SIC - S, Abhirami; Mouni, Nemalidinne Siva; Amuru, Sai Dhiraj; Kumar, Abhinav (IEEE Vehicular Technology Conference, 2024)
In fifth generation (5G) and beyond networks, the millimeter-wave frequency band is expected to cater to the ever increasing user demand for enhanced data rates. However, the denser deployments in mmwave with varying user velocities, will lead to frequent handovers (HOs), resulting in degradation of quality of service (QoS) for the end user in terms of both the number of HOs and lower throughput. Non-orthogonal multiple access (NOMA) is one of the promising radio access techniques for throughput enhancement in 5G and beyond networks. Motivated by this, we analyze the performance of a hybrid OMA-NOMA system considering the imperfections in successive interference cancellation (SIC) for various HO algorithms. We propose two HO algorithms: Algorithm 1 - the HO decision is based on the orthogonal multiple access (OMA) signal to interference-plus noise ratio (SINR) in the control plane, whereas, NOMA is only used for rate enhancements in the data plane; and Algorithm 2 - NOMA-based rates are taken into consideration for the HO decision. We compare the proposed algorithms with benchmark OMA based algorithms. Through extensive simulation we show that the proposed algorithms result in significant enhancement in throughput and reduction in the average number of HOs in the system.